Communities of Practice Fostering Peer-to-Peer Learning and Informal Knowledge Sharing in the Work Place - Hara, Noriko; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
The book offers two themes: one is about Communities of Practice (CoPs) and learning, the other is about social informatics approaches. First, in order to facilitate designing effective learning environments both online and offline, this book calls attention to the importance of CoPs to facilitate informal learning as part of professional development. Communities of Practice are informal networks that support a group of practitioners to develop a shared meaning and engage in knowledge building among the members. The concept of CoPs is rooted in situated cognition (Brown, Collins, & Duguid, 1989; Lave, 1988) and the socio-cultural theory (Vygotsky, 1978). The book examines how people share and construct their knowledge by using case studies of public defender$1 (Bs offices. Despite strong interests among practitioners and scholars, empirical studies of CoPs are sparse. Drawing on theories from situated cognition and social informatics, this book investigates what constitutes a community of practice and how members of the community create a shared meaning in workplaces with and without IT.s
Theoretical Foundation -- Ethnographic Accounts of a Community of Practice in Square County -- Characteristics of a Community of Practice in Square County -- Communities of Practice and Information Technologies in the Circle County Public Defender$1 (Bs Office -- Online Communities of Practice: Beyond Organizational Boundaries -- Toward an Understanding of Communities of Practice.s
Keywords: Computer science; Computer communication systems; Computers; Application software; Computers and civilization; Social sciences; Computer Science; Computer Communication Networks; Social Sciences, general; Computers and Society; Computer Appl. in Social and Behavioral Sciences; Information Systems and Communication Service; Professional & Vocational Education; Electronic books